(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Education and learning are the most crucial foundation of a growing economy worldwide. However, the academic system needs radical transformation; many online learning platforms are arising. Online learning, more pronounced as the Learning Management System (LMS), is emerging as a stepping stone towards bringing revolution to the educational sector and providing hands-on solutions to the problems in education in this new normal. In the modern world, students tend to rely greatly upon technologies to achieve dramatic performance outcomes, with an intense inclination towards cellular connectivity that enhances the learning output of the students and instructors. Assessments can be divided into two: assessment for learning and assessment as learning. Assessment for learning can be used by teachers to students, for example, to assess the student’s knowledge and skills to inform teaching and provide feedback to help those monitor and improve their learning skills. Assessment as learning will also occur when participating in an assessment, not only by tracking learning but also by affecting it. Students’ academic performance is routinely evaluated in relation to benchmarks to ascertain whether the current instruction and intervention are having a positive impact on student achievement or whether changes need to be made. This is an example of assessment for learning. The descriptive research methods were used in this study. The researchers floated a survey using Google Forms; a questionnaire dealing with people’s perceptions, knowledge, and experience would be classified as survey research. The researchers gathered data from fifty (50) target respondents from BSHM 4th-year students of the Bestlink College of the Philippines. The survey result revealed that the respondents’ profile explicitly responds to the clients of Bestlink College of the Philippines: Bachelor of Science in Hospitality Management 4th-year students were already noted, 27 people or 54% are 22 years old. In contrast, the profile of the respondents as to gender (female) is 62%. The student’s academic performance level relative to the Learning Management System (LMS) agrees that low-level and moderate-level academic performances play an important role in determining whether the LMS is applicable and appropriate to the student’s situation. The problem encountered by the 4th-year students when using the Learning Management System (LMS) concerning technical issues such as the loss of internet connection and time management. Based on the gathered data and conclusions drawn, the utilization of the findings of this study, and the inclusion of the following concerns that a guide on the assessment tools in LMS are. The service provider must fix the bug issues so that the LMS can be used easily, effectively, and simultaneously. Before taking quizzes such as your LMS exam, ensure you are in the right place/station with strong internet to avoid internet loss. Researchers have also found that using a learning management system to deliver instruction can have an impact on students’ performance, either favorably or unfavorably. Most students need to be more experienced in computer and online technology. Diversity of students in terms of the place where they belong, economic status, study habits, computer and online technology access, and experience must be considered. Therefore, using LMS has to be properly organized and differentiated based on the type and what the students need, emphasizing their learning goal and motivating them to regulate their task performance and work diligently.